An Intelligent System for Temperature Body Monitoring Using Arduino Platform - Mihaela MARIN; Alexandra BORŞAN; Laura-Daniela BURUIANĂ; Florin-Bogdan MARIN (The Annals of “Dunarea de Jos” University of Galati. Fascicle IX, Metallurgy and Materials Science)
An accurate measurement of the body temperature is a critical component in monitoring the human health, with applications ranging from clinical diagnostics to wearable health monitoring systems. Using the Arduino platform for body temperature monitoring provides an affordable, customizable and efficient solution for a wide range of applications, from personal care to patient monitoring in hospitals, this type of device can significantly contribute to improving health and safety. The MLX90614 sensor is an innovative and efficient solution for temperature measurement in the medical engineering field. With its outstanding accuracy and adaptability in measuring body temperature and medical devices, this device asserts itself as an indispensable tool in monitoring and managing the health of patients and medical devices in a variety of clinical and treatment settings.